Implementasi Metode Additive Ratio Assessment (ARAS) Untuk Seleksi Penerimaan Beasiswa Pada SMA Negeri 4 Bengkulu Tengah - Redi Satrio; Jusuf Wahyudi; Reno Supardi (UNIVED Press, 2023)
Abstract_Bengkulu Middle 4 State Senior High School is the only senior high school in Pagar Jati District, Central Bengkulu Regency. Selection of scholarships at SMA Negeri 4 Bengkulu Tengah is still done manually to select scholarship recipients and this results in errors and often inaccurate selection of scholarships. The Additive Ratio Assessment Method (ARAS) implementation application for selecting scholarship recipients at the Bengkulu Tengah 4 State Senior High School was created to assist teachers in making decisions easier in selecting the right scholarship recipients and assisting in the correct data collection. Processing in terms of data storage. Based on the results of the tests that have been carried out, functionally the application of the Additive Ratio Assessment (ARAS) Implementation Method for selecting scholarship recipients at Senior High School 4 Bengkulu Tengah is going well as expected.